The hermeneutical nexus of an undenominational Bible school : an application of philosophical hermeneutics and the literary analysis of Paul Ricoeur to the Carroll model for congregational studies - Damsell, Wilfred Ernest (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch Univesity, 2004.